Optimization of Biodiesel Production Parameters from Cucurbita maxima Waste Oil Using Microwave Assisted via Box-Behnken Design Approach - Ketema Beyecha Hundie (Journal of Chemistry)
The production of biodiesel from vegetables or fruits waste oils has high potential as renewable energy. The Cucurbita maxima wastes are massive source of oils, which are believed to indicate the possible sources of renewable energy whose biodiesel can be produced. Hence, the study explores the potential of the Cucurbita maxima wastes, for the production of biodiesel. In this study, the Soxhlet extraction method was used to extract Cucurbita maxima waste oil using an organic solvent. Through Box-Behnken design (BBD), the effects of methanol to oil molar ratio (6–10), catalyst concentration (2–6%), and reaction time (45–75 min) on the transesterification efficiency of methyl esters were investigated. The oil contents of Cucurbita maxima waste was found to be 44.6±0.21%. This oil was characterized, and after obtaining the pure characterized oil, biodiesel was produced using microwave assisted by the transesterification process. The optimum conversion efficiency of the Cucurbita maxima waste oil to fatty acid methyl ether was 97.76%, at the optimal parameters, methanol to oil ratio (8.4 : 1), catalyst concentration (3.14%), and reaction time (57.12 min). The results revealed that all parameters have a significant effect on the yield of biodiesel (p<0.0001). The physicochemical properties reveal that the Cucurbita maxima waste oil could be applied as a potential source of material for methyl ester production. The fatty acid profile of the oil indicated that it was mainly composed of unsaturated fatty acid, which ensures good flow properties of the fuel. The results of these studies showed the prospective of Cucurbita maxima wastes as a new potential feedstock for biodiesel production.